An efficient two-step synthesis of novel 2-amino-substituted pyrazolo[1,5-a][1,3,5] triazines (2012)
A series of novel 2-amino-substituted pyrazolo[1,5-a][1,3,5]triazines were selectively synthesized by a two-step reaction between 5-amino-3-hetaryl-1H-pyrazoles and hetaroyl isothiocyanates with subsequent amination and cyclization promoted by the couple HgCl2/TEA and DMF as solvent. This approach provided the title compounds in good to excellent yields and under mild reaction conditions. The structures of the new compounds were unambiguously established by spectroscopic and analytical techniques.